2020
DOI: 10.1038/s41467-020-16475-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic expression of p16INK4a in the epidermis induces Wnt-mediated hyperplasia and promotes tumor initiation

Abstract: Abstractp16INK4a (CDKN2A) is a central tumor suppressor, which induces cell-cycle arrest and senescence. Cells expressing p16INK4a accumulate in aging tissues and appear in premalignant lesions, yet their physiologic effects are poorly understood. We found that prolonged expression of transgenic p16INK4a in the mouse epidermis induces hyperplasia and dysplasia, involving high proliferation rates of keratinocytes not expressing the transgene. Continuous p16INK4a expression increases the number of epidermal papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…3B, 3C, Supplementary Table 4). Cdkn2a can exert ample anti-tumor effects (23,24), and when expressed in keratinocytes restricts proliferation, increases senescence and differentiation, and reduces tumor growth (25), consistent with its tumor-suppressive roles. Furthermore, recent work shows natural and immune checkpoint cancer immune control is achieved via Cdkn2a-dependent signaling, and interferons directly activate Cdkn2a (26).…”
Section: Unique Transcriptomic and Immune Changes By Sex In Micementioning
confidence: 68%
See 1 more Smart Citation
“…3B, 3C, Supplementary Table 4). Cdkn2a can exert ample anti-tumor effects (23,24), and when expressed in keratinocytes restricts proliferation, increases senescence and differentiation, and reduces tumor growth (25), consistent with its tumor-suppressive roles. Furthermore, recent work shows natural and immune checkpoint cancer immune control is achieved via Cdkn2a-dependent signaling, and interferons directly activate Cdkn2a (26).…”
Section: Unique Transcriptomic and Immune Changes By Sex In Micementioning
confidence: 68%
“…We show that the rate of DNA damage accumulation is equal in male and female mice exposed to equal doses of DMBA. (23,24) and cancer-immune responses (25,26). Based on this finding, we explored the possible differences in the mitotic rate of carcinogen-exposed epithelium between males and females, and found male epidermis was more proliferative than female skin.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly upregulated genes in the chemotherapy-treated samples cluster in pathways associated with pro-inflammation, apoptosis, cytokines and chemokines, and pro-cancer progression indicating that chemotherapy treatment creates a favourable, tumour-promoting microenvironment. These upregulated genes include: the Il6 family cytokine Lif, which promotes cell proliferation via STAT3 signalling and has been reported to promote breast cancer metastasis (Li et al, 2014; Niwa et al, 2009); Cxcl10, a SASP factor reported to enhance breast cancer lung metastasis (Pein et al, 2020; Perrott et al, 2017); the pro-tumourigenic factor Wnt5a (Azazmeh et al, 2020),(Kobayashi et al, 2018); as well as Ccl2 (MCP1), a potent macrophage chemoattractant, reported to play a role in cancer progression (Acosta et al, 2013; Park et al, 2012; Sanoff et al, 2014), and the related factors Ccl7 (MCP3) and Ccl8 (MCP2). In contrast, downregulated genes clustered primarily in humoural immunity pathways such as the B-cell surface antigens Cd79b, Ms4a1, and Cd19 and the B-cell lineage specific Pax5.…”
Section: Resultsmentioning
confidence: 99%
“…In some settings senescent cells were shown to inhibit tumourigenesis, by recruitment of immune cells or propagation of the senescence phenotype, [7][8][9] while in other settings such cells promoted tumourigenesis, by secretion of tumour stimulatory cytokines or the generation of an immune protective environment. [10][11][12][13] There is, however, overall little understanding of the prevalence of senescent cells in different tumour types, stages and cellular compartments and of their functions.…”
Section: Pancreasmentioning
confidence: 99%